Folklorna skupina v diaspori - Kunej, Rebeka (Etnolog. Nova vrsta (Ljubljana), 2016)
The article presents the activities of Slovene folklore ensembles in the diaspora, analyzes the characteristics of their repertoire and looks for the reasons why they differ from the practices of folklore ensembles in the homeland. Using the case of a folklore ensemble from North America, special attention is dedicated to the so-called cultural dance, which is a specific feature of folklore groups in the diaspora. Cultural dances are choreographed dances to Slovene folk pop music, performed in so-called national costumes. These practices have been rejected within the Slovene institutional frameworks, or treated as a negative phenomenon in folklore activities, while the communities in the diaspora (performers as well as audiences) often see them as an inherent part of their folklore performances.
Keywords: folklorne skupine; ljudski plesi; umetniški plesi; regionalni plesi; slovenski izseljenci; Slovenia; Slovenija; Severna Amerika; zgodovinski pregledi